The synopsis of the genus Gagea (Liliaceae) in Turkey - Tekşen, Mehtap; Karaman Erkul, Seher (Phytotaxa, 2015)
In this study, the synopsis of the genus Gagea taxa in Turkey is presented. According to Flora of Turkey, the genus has 26 taxa (25 species and one subspecies) in Turkey, however at the end of this study, the number has been increased to 29 species. It has been determined that G. foliosa, G. fibrosa, G. granatellii, G. taurica, and G. tenera do not actually occurr in Turkey. It has been confirmed that G. rigida, G. alexeenkoana, G. commutata, and G. chlorantha occur in the country. Diagnostic keys are provided for both sections and species within the genus.